(untitled) (Citizenship in Action: Extension and Culture Magazine, 2023)
Report of an Extension Project carried out at IFES, Venda Nova do Imigrante campus, called “Teatro Mundo”. The proposal began in early 2017, when the group of students began, with the teacher’s mediation, a series of theoretical and dramatic readings. For the production of the show, which would take place at the end of the same year, the choice fell on A farsa da boa laziness, by Ariano Suassuna, whose editing, from the rereading and rewriting of the script to the scenography, was up to the group. More than understanding the meaning that the expressions “theatre” and “theatrical spectacle” carry, the students achieved the perception of how important these activities are to refine us as humans; and more, to teach us to deal, humanistically, with the otherness that completes us and that also constitutes us.